Trade-offs between nutrient export, greenhouse gas balance and financial performance in continuous cover and rotation forestry in drained peatlands in northern Finland - Ahtikoski, Anssi; Repola, Jaakko; Hökkä, Hannu; Sarkkola, Sakari; Ojanen, Paavo; Haikarainen, Soili; Stenberg, Leena; Juutinen, Artti
Boreal peatlands comprise one of the largest terrestrial carbon pools, provide a variety of ecosystem services,and are important for biodiversity. The characteristic multifunctionality of peatland forests calls for research that is able to assess trade-offs between marketed (timber) and non-marketed (water quality, greenhouse gas balance) public goods. Once the trade-offs are revealed, it becomes feasible to pursue sustainable forest management. An openly available database was used to derive an empirical dataset representing a miniature of the Kiiminkijoki catchment in northern Finland, which was used for stand-level simulations (Motti stand simulator) and landscape-level optimisation in drained peatland forests. For each initial state, stand projections were simulated for rotation forestry (RF) and continuous cover forestry (CCF) management. The rationale was to investigate trade-offs between nutrient export, greenhouse gas balance and net present value (NPV). The cost efficiency of reducing greenhouse gas emissions and nutrient export was calculated by optimising forest management (both RF and CCF) within the Kiiminkijoki catchment. The results suggested that applying both RF and CCF in drained peatlands constitutes a highly cost-effective way to reduce greenhouse gas emissions, the cost range being € ~5–20 per tonne of CO2. However, the nitrogen equivalent (NE) cost of reducing nutrient export tends to be quite high (€ 17–58 kg-1) compared to values for mineral soils provided by existing literature. 2024